Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

Zoonotic Host Richness in the Global Wildland–Urban Interface - Rohan D. Simkin; Barbara A. Han; Volker C. Radeloff; Shannon LaDeau; Franz Schug; Karen C. Seto (Global Change Biology, 2025)
Where human settlements abut or intermix with wildlands, people may encounter animals that host zoonotic pathogens which can spillover to cause human disease. Known as the wildland–urban interface (WUI), this zone occupies around 5% of the Earth's surface and is home to 3.5 billion people. The rapid spread of SARS‐CoV‐2 has demonstrated the importance of understanding risk factors for disease among an increasingly urbanized population. However, the contribution of the WUI to zoonotic disease risk is poorly understood. Here, we show that low‐level host richness occurs throughout most of the global WUI, and 20% of the human WUI population live in zones of particularly high zoonotic potential, where more than 20 host species could occur. Zones of high zoonotic potential are concentrated in low–middle‐income countries (LMICs) across equatorial Africa, Brazil, Central America, and Southeast Asia where vulnerability is further elevated by widespread poverty, inadequate housing, and lack of easily accessible healthcare. Three of four people living in WUIs with high host richness (520 million people) are in LMICs. Of this population, 35% (183 million) live in and around cities in West, East, and South Africa. This means that WUI‐based populations of LMICs may face the double threat of high zoonotic potential and vulnerability to disease. Our results identify global priorities for monitoring exposure to zoonotic diseases in the rapidly expanding WUI.

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Analysis of the contribution of land consolidation to sustainable poverty alleviation under various natural conditions - Hanbing Li; Xiaobin Jin; Barbara Prack McCormick; Pablo Tittonell; Jing Liu; Bo Han; Rui Sun; Yinkang Zhou (Land Use Policy, 2023)

RNA sequencing reveals a complete picture of a homozygous missense variant in a patient with VPS13D movement disorder: a case report and review of the literature - Elizabeth K. Baker; Jingfen Han; William A. Langley; Michael A. Reott; Barbara E. Hallinan; Robert J. Hopkin; Wenying Zhang (Molecular Genetics and Genomics, 2023)

From raw data to publication: Introducing data editing at Ecology Letters - Peter H. Thrall; Jonathan Chase; John Drake; Nathalie Espuno; Stephane Hello; Vanessa Ezenwa; Barbara Han; Akira Mori; Helene Muller‐Landau (Ecology Letters, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Response to Merritts et al. (2023): The Anthropocene is complex. Defining it is not - Colin N. Waters; Martin J. Head; Jan Zalasiewicz; Francine M.G. McCarthy; Scott L. Wing; Peter K. Haff; Mark Williams; Anthony D. Barnosky; Barbara Fiałkiewicz-Kozieł; Reinhold Leinfelder; J.R. McNeill; Neil L. Rose; et al. (Earth-Science Reviews, 2023)

A cross-cultural study on odor-elicited life stage-associations - Martin Wendelin; Andrea Bauer; Elisabeth Buchinger; Lukas Danner; Eva Derndorfer; Vu Thi Minh Hang; Helene Hopfer; Marlies Wallner; Srinual Jantathai; Nina Julius; Imke Matullat; Dorota Majchrzak; et al. (Food Quality and Preference, 2023)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Unraveling the genetic complexities of combined retinal dystrophy and hearing impairment - Paulina Bahena; Narsis Daftarian; Reza Maroofian; Paola Linares; Daniel Villalobos; Mehraban Mirrahimi; Aboulfazl Rad; Julia Doll; Michaela A. H. Hofrichter; Asuman Koparir; Tabea Röder; Seungbin Han; et al. (Human Genetics, 2022)
Usher syndrome, the most prevalent cause of combined hereditary vision and hearing impairment, is clinically and genetically heterogeneous. Moreover, several conditions with phenotypes overlapping Usher syndrome have been described. This makes the molecular diagnosis of hereditary deaf–blindness challenging. Here, we performed exome sequencing and analysis on 7 Mexican and 52 Iranian probands with combined retinal degeneration and hearing impairment (without intellectual disability). Clinical assessment involved ophthalmological examination and hearing loss questionnaire. Usher syndrome, most frequently due to biallelic variants in MYO7A (USH1B in 16 probands), USH2A (17 probands), and ADGRV1 (USH2C in 7 probands), was diagnosed in 44 of 59 (75%) unrelated probands. Almost half of the identified variants were novel. Nine of 59 (15%) probands displayed other genetic entities with dual sensory impairment, including Alström syndrome (3 patients), cone-rod dystrophy and hearing loss 1 (2 probands), and Heimler syndrome (1 patient). Unexpected findings included one proband each with Scheie syndrome, coenzyme Q10 deficiency, and pseudoxanthoma elasticum. In four probands, including three Usher cases, dual sensory impairment was either modified/aggravated or caused by variants in distinct genes associated with retinal degeneration and/or hearing loss. The overall diagnostic yield of whole exome analysis in our deaf–blind cohort was 92%. Two (3%) probands were partially solved and only 3 (5%) remained without any molecular diagnosis. In many cases, the molecular diagnosis is important to guide genetic counseling, to support prognostic outcomes and decisions with currently available and evolving treatment modalities.

The macroecology and evolution of avian competence for Borrelia burgdorferi - Daniel J. Becker; Barbara A. Han (Global Ecology and Biogeography, 2021)
Aim Prediction of novel reservoirs of zoonotic pathogens would be improved by the identification of interspecific drivers of host competence (i.e., the ability to transmit pathogens to new hosts or vectors). Tick‐borne pathogens can provide a useful model system, because larvae become infected only when feeding on a competent host during their first blood meal. For tick‐borne diseases, competence has been studied best for Borrelia burgdorferi sensu lato ( Bb sl), which causes Lyme borreliosis. Major reservoirs include several small mammal species, but birds might play an under‐recognized role in human risk given their ability to disperse infected ticks across large spatial scales. Here, we provide a global synthesis of the ecological and evolutionary factors that determine the ability of bird species to infect larval ticks with Bb sl. Location Global. Time period 1983–2019. Major taxa studied Birds. Methods We compiled a dataset of Bb sl competence across 183 bird species and applied meta‐analysis, phylogenetic factorization and boosted regression trees to describe spatial and temporal patterns in competence, characterize its phylogenetic distribution across birds, reconstruct its evolution and evaluate the trait profiles associated with competent avian species. Results Half of the sampled bird species show evidence of competence for Bb sl. Competence displays moderate phylogenetic signal, has evolved multiple times across bird species and is pronounced in the genus Turdus . Trait‐based analyses distinguished competent birds with 80% accuracy and showed that such species have low baseline corticosterone, exist on both ends of the pace‐of‐life continuum, breed and winter at high latitudes and have broad migratory movements into their breeding range. We used these trait profiles to predict various likely but unsampled competent species, including novel concentrations of avian reservoirs within the Neotropics. Main conclusion Our results can generate new hypotheses for how birds contribute to the dynamics of tick‐borne pathogens and help to prioritize surveillance of likely but unsampled competent birds. Our findings also emphasize that birds display under‐recognized variation in their contributions to enzootic cycles of Bb sl and the broader need to consider competence in ecological and predictive studies of multi‐host pathogens.

Integrating data mining and transmission theory in the ecology of infectious diseases - Barbara A. Han; Suzanne M. O’Regan; John Paul Schmidt; John M. Drake (Ecology Letters, 2020)
Our understanding of ecological processes is built on patterns inferred from data. Applying modern analytical tools such as machine learning to increasingly high dimensional data offers the potential to expand our perspectives on these processes, shedding new light on complex ecological phenomena such as pathogen transmission in wild populations. Here, we propose a novel approach that combines data mining with theoretical models of disease dynamics. Using rodents as an example, we incorporate statistical differences in the life history features of zoonotic reservoir hosts into pathogen transmission models, enabling us to bound the range of dynamical phenomena associated with hosts, based on their traits. We then test for associations between equilibrium prevalence, a key epidemiological metric and data on human outbreaks of rodent‐borne zoonoses, identifying matches between empirical evidence and theoretical predictions of transmission dynamics. We show how this framework can be generalized to other systems through a rubric of disease models and parameters that can be derived from empirical data. By linking life history components directly to their effects on disease dynamics, our mining‐modelling approach integrates machine learning and theoretical models to explore mechanisms in the macroecology of pathogen transmission and their consequences for spillover infection to humans.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Gauging support for macroecological patterns in helminth parasites - Tad A. Dallas; A. Alonso Aguirre; Sarah Budischak; Colin Carlson; Vanessa Ezenwa; Barbara Han; Shan Huang; Patrick R. Stephens (Global Ecology and Biogeography, 2018)
Aim To explore spatial patterns of helminth parasite diversity, and to investigate three main macroecological patterns – (a) latitude–diversity relationships, (b) positive scaling between parasite and host diversity, and (c) species–area relationships – using a largely underutilized global database of helminth parasite occurrence records. Location Global. Methods We examined the London Natural History Museum’s collection of helminth parasite occurrence records, consisting of over 18,000 unique host species and 27,000 unique helminth parasite species distributed across over 350 distinct terrestrial and aquatic localities. Results We find support for latitudinal gradients in parasite diversity and a strong relationship between host and parasite diversity at the global scale. Helminth species diversity–area relationships were not detectable as a function of host body mass, but larger geographic areas supported higher parasite richness, potentially mediated through higher host richness. Main conclusions Our findings indicate that helminth parasites may obey some of the macroecological relationships found in free‐living species, suggesting that parasites may offer further support for the generality of these patterns, while offering interesting counterexamples for others. We conclude with a discussion of future directions and potential challenges in the newly emerging macroecology of infectious disease.

Global Mammal Parasite Database version 2.0 - Patrick R. Stephens; Paula Pappalardo; Shan Huang; James E. Byers; Maxwell J. Farrell; Alyssa Gehman; Ria R. Ghai; Sarah E. Haas; Barbara Han; Andrew W. Park; John P. Schmidt; Sonia Altizer; et al. (Ecology, 2017)
Illuminating the ecological and evolutionary dynamics of parasites is one of the most pressing issues facing modern science, and is critical for basic science, the global economy, and human health. Extremely important to this effort are data on the disease‐causing organisms of wild animal hosts (including viruses, bacteria, protozoa, helminths, arthropods, and fungi). Here we present an updated version of the Global Mammal Parasite Database, a database of the parasites of wild ungulates (artiodactyls and perissodactyls), carnivores, and primates, and make it available for download as complete flat files. The updated database has more than 24,000 entries in the main data file alone, representing data from over 2700 literature sources. We include data on sampling method and sample sizes when reported, as well as both “reported” and “corrected” (i.e., standardized) binomials for each host and parasite species. Also included are current higher taxonomies and data on transmission modes used by the majority of species of parasites in the database. In the associated metadata we describe the methods used to identify sources and extract data from the primary literature, how entries were checked for errors, methods used to georeference entries, and how host and parasite taxonomies were standardized across the database. We also provide definitions of the data fields in each of the four files that users can download.

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Transcription factors that directly regulate the expression of CSLA9 encoding mannan synthase in Arabidopsis thaliana - Won-Chan Kim; Ida-Barbara Reca; YongSig Kim; Sunchung Park; Michael F. Thomashow; Kenneth Keegstra; Kyung-Hwan Han (Plant Molecular Biology, 2014)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Individual and combined effects of multiple pathogens on Pacific treefrogs - John M. Romansic; Pieter T. J. Johnson; Catherine L. Searle; James E. Johnson; Tate S. Tunstall; Barbara A. Han; Jason R. Rohr; Andrew R. Blaustein (Oecologia, 2011)

Species-level correlates of susceptibility to the pathogenic amphibian fungus Batrachochytrium dendrobatidis in the United States - Betsy A. Bancroft; Barbara A. Han; Catherine L. Searle; Lindsay M. Biga; Deanna H. Olson; Lee B. Kats; Joshua J. Lawler; Andrew R. Blaustein (Biodiversity and Conservation, 2011)

Experimental examination of the effects of ultraviolet-B radiation in combination with other stressors on frog larvae - Catherine Laura Searle; Lisa K. Belden; Betsy A. Bancroft; Barbara A. Han; Lindsay M. Biga; Andrew R. Blaustein (Oecologia, 2010)

Ancient behaviors of larval amphibians in response to an emerging fungal pathogen, Batrachochytrium dendrobatidis - Barbara A. Han; Paul W. Bradley; Andrew R. Blaustein (Behavioral Ecology and Sociobiology, 2008)

Using oligonucleotide suspension arrays for laboratory identification of bacteria responsible for bacteremia - Xiao-li Hou; Han-liang Jiang; Qing-yi Cao; Li-ying Zhao; Barbara J. Chang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2008)

Use of bioluminescent imaging to investigate the role of nuclear factor-κΒ in experimental non-small cell lung cancer metastasis - Georgios T. Stathopoulos; Taylor P. Sherrill; Wei Han; Ruxana T. Sadikot; Vasiliy V. Polosukhin; Barbara Fingleton; Fiona E. Yull; Timothy S. Blackwell (Clinical & Experimental Metastasis, 2008)

Interspecific Variation in Susceptibility of Frog Tadpoles to the Pathogenic Fungus Batrachochytrium dendrobatidis - ANDREW R. BLAUSTEIN; JOHN M. ROMANSIC; ERIN A. SCHEESSELE; BARBARA A. HAN; ALLAN P. PESSIER; JOYCE E. LONGCORE (Conservation Biology, 2005)
As part of an overall biodiversity crisis many amphibian populations are in decline throughout the world. Numerous causes have been invoked to explain these declines. These include habitat destruction, climate change, increasing levels of ultraviolet radiation, environmental contamination, and the introduction of non‐native species and diseases. Several types of pathogens have been implicated in contributing to amphibian population declines: viruses, bacteria, oomycetes, and fungi. One particular fungus, the chytridiomycete Batrachochytrium dendrobatidis may have caused amphibian population declines in several regions. This pathogen causes chytridiomycosis, which is fatal to newly metamorphic and adult amphibians of certain species. We present experimental evidence that larval stages may also be susceptible to exposure to Batrachochytrium . There was, however, differential sensitivity to B. dendrobatidis in larvae we examined. In laboratory experiments, larval western toads ( Bufo boreas ) exposed to B. dendrobatidis experienced increased mortality and behaviors that suggested they were affected by exposure compared with unexposed control tadpoles. Larvae of Cascades frogs ( Rana cascadae ), bullfrogs ( R. catesbeiana ), and Pacific treefrogs ( Hyla regilla ) did not die after exposure to Batrachochytrium and appeared to behave normally. R. cascadae larvae exposed to B. dendrobatidis , however, showed an increase incidence in mouthpart abnormalities, a characteristic effect of chytridiomycosis, compared with unexposed controls. These results show that Batrachochytrium can negatively affect some species of amphibians at the larval stage and not others. The implications of interspecific variation in susceptibility to fungal infection are broad.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)